Characterization of morbidity in children/adolescents with continuous and complex care admitted to pediatric intensive care (Research, Society and Development, 2022)
Objective: to analyze the morbidity profile of children/adolescents with continuous and complex care discharged from a Pediatric Intensive Care Unit and the factors associated with the need for continuous and complex care. Method: quantitative, retrospective, documentary study, developed from the descriptive and analytical statistical analysis of medical records of children/adolescents with continuous and complex care in a Pediatric Intensive Care Unit in the state of Rio Grande do Sul. Data analysis was performed using descriptive and analytical statistics. Results: diseases of the respiratory system were the main causes of admission to this unit. Children aged up to one year, white and male predominated. Previous history of morbidities, use of continuous medication, mechanical ventilation and health technology were associated with the need for continuous and complex care. Conclusion: there are conditions that predispose the need for continuous and complex care, implying the systematization of actions aimed at reducing its need and the number of readmissions for this clientele.